2022
DOI: 10.1101/2022.04.01.22273073
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trans-border transfer of human biological materials in collaborative biobanking research: Perceptions and experiences of researchers in Uganda

Abstract: IntroductionThe study aimed to explore researchers’ perceptions and experiences on the transfer of human biological materials in international collaborative research.MethodsThis was a descriptive convergent parallel survey that randomly recruited 187 researchers involved in biobanking and/or genetics research. Data were collected using a self-administered tool that had both open and closed ended questions.ResultsMajority of respondents were male scientists (53.5%) with a mean research experience of 12.2 (SD 6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…As it turns out, these scientists were also project leaders and lead applicants to grants. Participants had varying knowledge about the processes involved in sample sharing and biobanking, and this is reported elsewhere (Mwaka et al, 2022; Mwaka & Munabi, 2022; Mwaka et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…As it turns out, these scientists were also project leaders and lead applicants to grants. Participants had varying knowledge about the processes involved in sample sharing and biobanking, and this is reported elsewhere (Mwaka et al, 2022; Mwaka & Munabi, 2022; Mwaka et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…This is supported by Labuschaigne et al 33 who reported that HBMs may be leaving South Africa without export permits or MTAs during collaborative research. Mwaka and Munabi 34 , who undertook a similar study on perceptions and experiences on the transfer of HBMs in international collaborative research in Uganda, reported that the development of an MTA and its implementation lacked transparency.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, negotiating the diverse data protection laws and regulations across countries involved in the biobanking initiative and harmonizing privacy practices to meet the requirements of multiple jurisdictions can be a complex endeavor. Moreover, complying with restrictions on cross-border data transfer imposed by various countries poses a significant challenge 60 . Some countries have stringent regulations specifying where data can be stored and processed, introducing hurdles for international collaboration 61 .…”
Section: Ethical Challengesmentioning
confidence: 99%